Effect of pore geometry on ultra-densified hydrogen in microporous carbons. (March 2021) - Tian, Mi; Lennox, Matthew J.; O'Malley, Alexander J.; Porter, Alexander J.; Krüner, Benjamin; Rudić, Svemir; Mays, Timothy J.; Düren, Tina; Presser, Volker; Terry, Lui R.; Rols, Stephane; Fang, Yanan; et al.
Abstract: Our investigations into molecular hydrogen (H2 ) confined in microporous carbons with different pore geometries at 77 K have provided detailed information on effects of pore shape on densification of confined H2 at pressures up to 15 MPa. We selected three materials: a disordered, phenolic resin-based activated carbon, a graphitic carbon with slit-shaped pores (titanium carbide-derived carbon), and single-walled carbon nanotubes, all with comparable pore sizes of <1 nm. We show via a combination of in situ inelastic neutron scattering studies, high-pressure H2 adsorption measurements, and molecular modelling that both slit-shaped and cylindrical pores with a diameter of ∼0.7 nm lead to significant H2 densification compared to bulk hydrogen under the same conditions, with only subtle differences in hydrogen packing (and hence density) due to geometric constraints. While pore geometry may play some part in influencing the diffusion kinetics and packing arrangement of hydrogen molecules in pores, pore size remains the critical factor determining hydrogen storage capacities. This confirmation of the effects of pore geometry and pore size on the confinement of molecules is essential in understanding and guiding the development and scale-up of porous adsorbents that are tailored for maximising H2 storage capacities, in particular for sustainable energy applications. Graphical abstract: Image 1